‘Neutrality’, Muslimness and the whiteness of RE professionalism - Vince, Matthew (Journal of Religious Education, 2020)
There has been longstanding criticism of the whiteness of the professional discourses in teaching. Bariso (Race Ethn Educ 4(2):167-184, https://doi.org/10.1080/713693054, 2001) writes that where whiteness is constructed as being professional then blackness is constructed as unprofessional, in turn excluding blackness from the construction of the teacher. Similarly, Bhopal (Br J Educ Stud, 63(2):197-211, https://doi.org/10.1080/00071005.2015.1005045, 2015) argues that this presents a clash between embodying blackness and embodying the teacher. With the turn to research surrounding Muslim teachers, attributes of Muslimness have also been shown to be a source of marginalisation within school contexts (Shah in Education, leadership and Islam: theories, discourses and practices from an Islamic perspective, Routledge, London, 2016). Some scholarship has reflected on issues surrounding embodiment and ‘body-works’ of RE teaching’s professional discourses (Bryan and Revell in Br J Educ Stud 59(4):403-419, https://doi.org/10.1080/00071005.2011.602328, 2011; Everington in Br J Religious Educ 36(2):155-173, https://doi.org/10.1080/01416200.2013.820169, 2014; Vince in J Beliefs Values, https://doi.org/10.1080/13617672.2019.1686732019, 2019). Such empirical studies have shown that embodying faith is perceived to be at odds with notions of RE teacher professionalism, particularly around notions of ‘neutrality’ (Everington in Br J Relig Educ, 38(2):177-188, https://doi.org/10.1080/01416200.2016.1139892, 2016). Despite the concept of ‘neutrality’ being increasingly criticised (Franken and Loobuyck in Br J Relig Educ, 39(1):1-6, https://doi.org/10.1080/01416200.2016.1218219, 2017), embodying ‘neutrality’ remains an important commitment. This has clear implications for (hyper)visible religious bodies (Jeldtoft, in: Dessing et al. (eds) Everyday Lived Islam in Europe, Routledge, London, 2016). Accordingly, in this paper I explore how ‘Muslim RE teachers’ manage their identities in relation to ‘being neutral’. For these teachers, ‘becoming neutral’ was the formative part of becoming an RE teacher. However, this was particularly challenging due to the hypervisibility of their Muslimness, particularly for female Muslim teachers. These challenges are then framed as an issue of whiteness, disproportionally affecting those who do not fit the white teacher norm. I end on arguing that there is a pressing need to change how ‘neutrality’ is understood.